Ontology of manufacturing enginneering - Cetiner, Beytullah Gultekin; Ismail, Ahmad Faris; Hassan, Azmi (Karabuk University, 2009)
Manufacturing sector in Malaysia is the main driver in the economy. Therefore, most of the universities in Malaysia have Manufacturing Engineering Programs. Actually number of Manufacturing Engineering Programs is higher than Industrial Engineering Programs throughout the country. The related departments in Higher Education Organizations make frequently Benchmarking studies to compare their Manufacturing Engineering Programs with the other universities not only in the country but also in the region. Manufacturing Engineering Department at IIUM has been conducting another major curriculum review to update the program based on the recent changes in Faculty Outcomes for New Accreditation period by taking stakeholders’ feedback into account. This paper proposes the use of a data-model based Ontology of Manufacturing for reviewing and changing the Manufacturing Engineering Programs and gives a kind of benchmarking for the new Manufacturing Engineering Program at IIUM.